Analysis of Politeness Maxims in the Film Layangan Putus: Study of the Speeches of the Characters Kinan and Aris - Roysa, Mila; Rokhman, Fathur; Rustono, Rustono; Mardikantoro, Hari Bakti (Proceedings of International Conference on Science, Education, and Technology, 2024)
This research aims to describe the maxims of politeness in the film Kite Putus in the speech of the characters Kinan and Aris. The research uses Leech's theory of language politeness principles. The type of research is qualitative research. The data collection method uses the method of listening to stories and recording dialogue utterances of characters in films. The research data source is a series of broken kite films, and the data analysis technique uses three stages consisting of introduction or identification, grouping or qualification, and data interpretation. The research results explain that there are maxims of politeness including the maxims of wisdom, generosity, humility, appreciation, simplicity, consensus, and sympathy.